Stres akademik siswa yang akan menghadapi ujian nasional berdasarkan jenis kelamin - Anisa Dwi Astuti; Taufik Taufik; Ifdil Ifdil (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
This research is based on several problems about unreadiness and the success of students in facing the national exam which one of them is influenced by academic stress condition. The research objective to describe the academic stress of male and female students, and to identify the difference. This research uses the quantitative method with descriptive and comparative approach, which has sample 215 using purposive sampling technique. The instruments used stress academic stress scale (SAS). The data analyzed by using persentage, and differential with SPSS for windows release 20. The research findings show the academic stress majority on medium category (40,9%), the academic stress of male students are majority on medium category (45%), and female students are majority on medium category (39%). There is significant difference between the academic stress of male and female students. This research recommanded to counselor for reduce the students academic stress before national exams.